Attracting international research professionals to EU smart regions: evidence from Tuscany. - Katerina Stancova (European Regional Science Association (ERSA), 2014)
Human resources is one of the main assets of the regional innovation systems. The development and accumulation of human resources is a crucial prerequisite to keep regional R&I industries highly performing and internationally competitive. Yet, regional policies to attract international research professionals (IRPs) are still underdeveloped for a number of reasons. It is crucial to understand the role of regions in managing IRP migration, as well as factors and obstacles to IRP immigration in order to design effective policy measures. It is argued that the factors that influence the size, composition and distribution of IRPs within a territory are place-based, and they are structural (organisational, policy-related and economic) as well as non-pecuniary (professional, personal, cultural, lifestyle preferences). The framework is interrogated via a case study of Tuscany. Particular attention is paid to organisational, policy-related, economic and human factors. The paper concludes by offering a discussion of policies to be implemented at different levels of governance to improve attraction and recruitment potential, and to achieve the ultimate goal of sustainable management of regional research capacities.
Keywords: J61; R23; 330